1999
DOI: 10.1007/s100249900161
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Membrane Histology in Preterm Premature Rupture of Membranes: Comparison to Controls, and between Antibiotic and Placebo Treatment

Abstract: The objectives of this study were to test the hypotheses that antibiotic therapy will alter the histologic appearance of fetal membranes in preterm premature rupture of membranes (pPROM), and that the membrane histology will demonstrate distinct differences between term and preterm rupture of membranes. We also wished to test interobserver variability of pathologists. Placental membranes were sampled from 268 women participating in a randomized placebo-controlled trial of antibiotic therapy for pPROM at 24-32 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 8 publications
1
9
1
3
Order By: Relevance
“…This benefit occurred in patients with demonstrable intra-amniotic infection/inflammation at the beginning of the therapy, but not in patients without this condition. Our findings are in contrast to those previously reported, indicating that a combination of amoxicillin and erythromycin for a short period of time did not reduce the frequency of acute histologic chorioamnionitis [96,202,203]. Of interest, in a randomized clinical trial in which the efficacy of cefazolin, cefazolin plus erythromycin, or cefazolin plus clarithromycin for seven days was compared, the use of cefazolin with clarithromycin was associated with a reduction in the percentage of patients with severe funisitis.…”
Section: Discussioncontrasting
confidence: 99%
“…This benefit occurred in patients with demonstrable intra-amniotic infection/inflammation at the beginning of the therapy, but not in patients without this condition. Our findings are in contrast to those previously reported, indicating that a combination of amoxicillin and erythromycin for a short period of time did not reduce the frequency of acute histologic chorioamnionitis [96,202,203]. Of interest, in a randomized clinical trial in which the efficacy of cefazolin, cefazolin plus erythromycin, or cefazolin plus clarithromycin for seven days was compared, the use of cefazolin with clarithromycin was associated with a reduction in the percentage of patients with severe funisitis.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies in humans have suggested an association between acute chorioamnionitis and neurodevelopmental disorders [136,151159]. The observation that the administration of ampicillin and erythromycin in the randomized clinical trial conducted by Mercer et al [100] did not result in a lower rate of funisitis (compared to the placebo group) [160] indicates that short-term antimicrobial therapy did not reduce the likelihood of a fetal inflammatory response [79]. This observation is consistent with a subsequent report indicating that there was no change in the concentrations of inflammatory cytokines in umbilical cord blood after the administration of antibiotics [161].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings regarding maternal systemic inflammatory markers, we have previously found that antibiotic treatment during conservative management of preterm PROM does not significantly impact histological findings in the placenta and membranes. (25) It is plausible that the inflammatory cascade cannot be stopped once initiated. Alternatively it may also be possible that intrapartum events obscure the effects of antibiotics on placental and cytokine findings regardless of extended latency and absence of overt intrauterine infection until near the time of delivery.…”
Section: Commentmentioning
confidence: 99%